A study on prevalence of depression among adults attending International Islamic University Malaysia (IIUM) Family Health Clinic, Kuantan Pahang, Malaysia - Che' Man, Mohamad; Yusof, Muhammad Zubir; A, Ahmad Azri; S, Muhammad Mustaufiq; MR, Mohammad Afif (Science Forecast Publications, 2019)
Introduction: Depression is a common mental disorder among the general population. According to WHO, people with depression is experiencing boredom in things they usually enjoy, loss of capability in self-care and have long standing period of sadness? The impact of depression falls greatly onto the individuals, family members and the community. Methodology: A cross-sectional study was conducted among 250adults attending IIUM FHC Kuantan. A validated self-reported questionnaire including sociodemographic, socioeconomics and Patient Health Questionnaire (PHQ-9) was distributed from 15th to 26th July 2019. Descriptive statistics were used to measure the prevalence of depression. Chi- square test was used to measure the association between risk factors and depression. Results: The prevalence of depression among adults attending IIUM FHC Kuantan was 10.4% the statistically significant associated factors were marital status (p-value=0.045) and working status (p-value=0.014). Conclusion: One in ten of adults attending IIUM FHC, Kuantan, Pahang had depression and the significantly associated factors were marital status and employment status. Keywords: Depression; Cross-sectional study; Health clinic; Patient Health Questionnaire (PHQ-9)